Business Groups in Emerging Markets: Paragons or Parasites? - Khanna, Tarun; Yafeh, Yishay (Journal of Economic Literature, 2007)
Diversified business groups, consisting of legally independent firms operating across diverse industries, are ubiquitous in emerging markets. Groups around the world share certain attributes but also vary substantially in structure, ownership, and other dimensions. This paper proposes a business group taxonomy, which is used to formulate hypotheses and present evidence about the reasons for the formation, prevalence, and evolution of groups in different environments. In interpreting the evidence, the authors pay particular attention to two aspects neglected in much of the literature: the circumstances under which groups emerge and the historical evidence on some of the questions addressed by recent studies. They argue that business groups are responses to different economic conditions and that, from a welfare standpoint, they can sometimes be “paragons” and, at other times, “parasites.” The authors conclude with an agenda for future research.